LRRK2 Contributes to Secondary Brain Injury Through a p38/Drosha Signaling Pathway After Traumatic Brain Injury in Rats - Rui, Qin; Ni, Haibo; Gao, Fan; Dang, Baoqi; Li, Di; Gao, Rong; Chen, Gang (Frontiers in Cellular Neuroscience, 2018)
Leucine-rich repeat kinase 2 (LRRK2) is widely expressed in the brain and exerts neurotoxicity in Parkinson's disease. The p38/Drosha signaling activation has been reported to increase cell death under stress. This study was designed to investigate the potential role and mechanism of LRRK2 in secondary brain injury after traumatic brain injury (TBI). A total of 130 male Sprague-Dawley rats were examined using a weight-drop model of TBI. The rats received the specific LRRK2 inhibitor PF-06447475 or LRRK2 pDNA alone or in combination with Drosha pDNA. Real-time PCR, Western blot, immunofluorescence, neuronal apoptosis, brain water content, and neurological score analyses were conducted. Our results showed that after TBI, endogenous LRRK2 expression and p38 phosphorylation were increased, whereas Drosha expression was inhibited. Administration of the LRRK2 inhibitor PF-06447475 significantly reduced neuronal apoptosis, brain water content, and blood-brain barrier permeability 12 h after TBI and ameliorated neurological deficits 72 h after TBI, which was concomitant with decreased p38 phosphorylation and increased Drosha expression. Conversely, LRRK2 overexpression induced the opposite effect. Moreover, the neurotoxic effects of LRRK2 on TBI were also eliminated by Drosha overexpression. Altogether, these findings demonstrate the importance of TBI-induced LRRK2 upregulation during the induction of post-traumatic neurological injury, which may be partially mediated through a p38/Drosha signaling pathway.